Foliar application of phosphoric acid mitigates oxidative stress induced by herbicides in soybean, maize, and cotton crops - Viveiros, Josiane [UNESP]; Moretti, Luiz Gustavo [UNESP]; Pacola, Marcela [UNESP]; Jacomassi, Lucas Moraes [UNESP]; de Souza, Fernanda Marcolan [UNESP]; Rodrigues, Vitor Alves [UNESP]; Bossolani, João William [UNESP]; Portugal, José Roberto [UNESP]; Carbonari, Caio Antonio [UNESP]; Crusciol, Carlos Alexandre Costa [UNESP] (Elsevier, 2024)
Foliar fertilization presents a potential solution in alleviating oxidative stress triggered by herbicide exposure. Enhancing our comprehension of the interplay between foliar fertilization, oxidative stress, and herbicide application is pivotal for enhancing crop yield. Carfentrazone, a herbicide, prompts the buildup of reactive oxygen species, leading to detrimental effects on cell membranes and the manifestation of chlorotic spots on leaves. This research administered carfentrazone-ethyl to soybean, maize, and cotton to induce stress. The herbicide application was followed by foliar application of phosphorus (H3PO4) to evaluate its effect on phytotoxicity recovery. The evaluations included leaf nutritional analyses, gas exchange measurements (photosynthesis, stomatal conductance, substomatal CO2 concentration, and Leaf transpiration), photosynthetic pigments (chlorophylls and carotenoids), oxidative stress indicators (MDA, H2O2, SOD, CAT and APX), and productivity parameters (height, number of branches, pods, grains, 100-grain weight, and yield), in addition to the activity of the enzyme Rubisco (ribulose-1,5-bisphosphate carboxylase/oxygenase), which is crucial for carbon fixation and the photosynthetic efficiency of plants. Phosphorus (P) improved chlorophyll levels by up to 28.8% and Rubisco activity by up to 24.8%, leading to increases in the net photosynthetic rate by up to 40.2%, stomatal conductance, water use efficiency, and carboxylation. In addition, foliar P fertilization enhanced antioxidant metabolism, with reductions in markers of oxidative stress (H2O2 and MDA) by up to 39.1%. Collectively, these effects of foliar P fertilization increased the productivity of the three crops by up to 55.9%, indicating that foliar supplementation with P is an effective strategy to mitigate phytotoxicity symptoms. In soybeans at the V4 and V6 stages, it has been shown to improve net photosynthesis, enhance Rubisco activity, and reduce oxidative stress. In maize, the V4 stage proved to be more effective, increasing Rubisco activity and improving productivity. For cotton, the B1 stage was more beneficial, resulting in increased boll weight and fiber yield. This study introduces an innovative approach of foliar P-supplementation to mitigate herbicide-induced oxidative stress in crops. This management strategy enhances crop resilience, improves yield stability, and provides a sustainable solution to a critical challenge in modern agriculture.
Keywords: Antioxidant mechanisms; Herbicide-induced stress; Phosphorus supplementation; Plant metabolic responses